Developing nursing research in the United Arab Emirates: a narrative review. (11th October 2017) - McCreaddie, M.; Kuzemski, D.; Griffiths, J.; Sojka, E.M.; Fielding, M.; Al Yateem, N.; Williams, J.J.
Abstract : Aim: This article identified, critically analysed and synthesized the literature on international nursing and midwifery research capacity building and standards. Background: The United Arab Emirates is heavily dependent up on expatriate nurses. Only 4% of nurses working within the country are Emirati. The nation is therefore committed to developing nurses and nursing as a profession. Introduction: The United Arab Emirates' Nursing and Midwifery Council was formed in 2009 and initially focused on regulation, education and specialization. This review was undertaken to inform the work of the Council's newly established Scientific Research Sub‐Committee. Methods: A rapid narrative review was conducted using the Cumulative Index of Nursing and Allied Health Literature database, key words, Boolean operators, parameters and a journal‐specific search. An inclusion/exclusion criterion was identified. Results: The search provided 332 articles with 45 included in the final review. The literature on nursing research 'standards' and 'capacity building' is diverse and inconsistent across continents and in approaches. Discussion: Nursing research has evolved to varying degrees across the globe. Nevertheless, irrespective of the locale, there are similar problems encountered in growing research, for example nursing faculty shortage, lack of collaborative research, funding. There are also specific challenges in the Middle East and North Africa region. Limitations: The review was constrained by time and access. Conclusion and implications for nursing policy: There are specific challenges for the United Arab Emirates. However, the country is well placed to learn from the experiences of colleagues elsewhere. Time and commitment is required to build the solid foundations necessary to ensure robust, sustained growth. Identifying research capacity as both a process and outcome at the outset may also assist. Further, it may be prudent to consider initiating a Gulf Coast Countries' collaborative approach to building research capacity to harness scare resources and create a larger critical mass.